Prevalence of Pterygium and Outcome of Pterygium Surgery in Hilly Western Nepal: A Hospital based Study - Manandhar, Laxmi Devi; Rai, Salma KC; Gurung, Shanti; Shrestha, Koshal; Godar, Manita; Hirachan, Anjita; Shrestha, Ruchi (Journal of Lumbini Medical College, 2017)
Introduction: Surgical removal is the treatment of choice for pterygium; however, prevention of recurrence is a challenge. Several techniques have been tried to reduce the fibro-vascular activity aiming to reduce rate of recurrence such as B-irradiation, conjunctival and limbal auto-grafting, anti-mitotic drugs, and amniotic membrane transplantation. This study reports the magnitude of the disease in a hilly region of western Nepal and outcome of excision and conjunctival autografting for pterygium surgery.Methods: A prospective study was done from 1st July 2015 to 31st December 2016 in which all patients with primary pterygium presented to Palpa Lions Lacoul Eye Hospital from 1st July 2015 to 30th June 2016 were treated and followed up for next six months. Patients were treated medically or surgically as indicated. Data on age, sex, visual acuity, extent of disease, treatment modality, complications, and outcome were collected and analyzed by descriptive statistics, Chi-square test, t-test, and Anova tests. P value less than 0.05 was considered significant.Results: There were 18,960 patients in total attending hospital for various conditions among which 290 (1.53%) had pterygium. There were 186 (64.1%) female and 104 (35.9%) male and this difference was significant (p